Recombination and dynamics of transposable elements in natural populations. A drosophilist’s view - Kozeretska, I.A. (Вiopolymers and Cell, 2011)
The concept of the tight link between crossing over and the dynamics of transposable elements is presented. The behavior of transposable elementsinfluences the processes of homologous recombination, both at the moment of activation and as a result the changes in a genome caused by active transposition of the autonomous nucleotide sequences. Keywords: crossing over, transposable elements, drosophila.